Fatores climáticos e comportamentais de emas (Rhea americana, Linnaeus, 1758) alimentadas com diferentes dietas - Gadelha, Ana Indira Bezerra Barros (Universidade Federal Rural do Semi-Árido, 2018)
With the increase of greater rhea (Rhea Americana) as an animal of production (meat, leather, feathers, eggs and fat) the commercial exploitation has increased and also the interest for research related to these animals, because other animals are still used (ostrich and emu) as source of foundation to meet the nutritional, physiological, behavioral and environmental demands that affect these animals. It is known that the behavior can be influenced by several factors such as: environment, diet and management. The aim of this work was to evaluate the behavior and effect of the environment under greater rhea, from 30 to 90 days of age, fed with balanced diet. The experimental groups consisted of two different diets: conventional diet and alternative diet. They were with base in the literature evaluated the related behaviors (walking for the enclosure, pecking, walking to and fro, foraging, lying, sleeping, looking for the light, eating ration, drinking water, eating fruit, coprophagy, stereotypy) the diet (alternative and formulated), to the schedules of observation (7:00, 12:00 and 17:00), to the atmosphere (corporal temperature, relative humidity and speed of the wind) and the corporal (they were checked through images as way no invasive of measuring the temperature) temperature in the experimental groups. The behaviors observations were made through the method of Scan Sampling, the environmental data were collected through the term-higro-anemometer and black globe and the data of corporal temperature through thermal camera. The test used for the data behaviors was it of Kruskal Wallis to 5% of probability and for the environmental data, the one of Tukey to 5% of probability. The behavior suffered influence of the diet in some varied analyzed (sleeping and stereotypy that you/they were significant in the alternative diet) and it suffered influence of the schedule in all the variables, the environmental data varied with the schedules and they didn't vary with the diets and the corporal temperature stayed constant in every schedule, independent of the diet.
Monografia
Keywords: Análise comportamental; Nutrição animal; Rheacultura; Rhea americana; Behavioral analysis; Animal nutrition; Rhea culture; Rhea americana; CIENCIAS AGRARIAS::ZOOTECNIA